EFFECTIVENESS OF TOPICAL BREAST MILK IN ACCELERATING UMBILICAL CORD SEPARATION IN NEWBORNS - Halisah Halisah; Intan Idiana Hassan; Farida Tandi Bara (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Umbilical cord infection remains a significant contributor to neonatal morbidity and mortality, particularly in developing countries. Proper cord care is essential to prevent infection and accelerate cord separation. Topical breast milk contains antimicrobial and anti-inflammatory components that may enhance healing. This quasi-experimental study with a two-group comparison was conducted at a regional hospital involving 60 newborns selected through purposive sampling and divided into topical breast milk and dry open care groups. Data were analyzed using independent t-test with a significance level of p<0.05. The mean cord separation time in the topical breast milk group was 5.13±0.83 days, compared to 6.26±0.70 days in the dry open group, with a statistically significant difference (p<0.001) and a very large effect size (Cohen’s d=1.47). Topical breast milk is more effective in accelerating umbilical cord separation than dry open care and can be recommended as a simple, safe, and cost-effective evidence-based practice in neonatal care.